TLR4-MyD88 pathway promotes the imbalanced activation of NLRP3/NLRP6 via caspase-8 stimulation after alkali burn injury. (November 2018) - Chen, Hui; Li, Yonghao; Gu, Jianjun; Yin, Lin; Bian, Fang; Su, Lishi; Hong, Yanhua; Deng, Yang; Chi, Wei
Abstract: Alkali burn (AB) is one of the most serious ocular traumas in the world, characterized by extreme ocular surface disorders, critical secondary dry eye and irreversible vision loss. The exact mechanisms involved are unknown. Innate immunity, including the involvement of Toll-like receptors (TLRs) and NOD-like receptors (NLRs), is believed to participate in the pathogenesis of the epithelia, but the exact mechanisms by which TLRs transduce signals to NLRs and downstream molecules to initiate innate immunity remain poorly defined. In this present study, we used murine models of AB and AB concomitant desiccating stress (DS) to investigate the potential functions and mechanisms of TLR4 in regulating NLRP3 and NLRP6 during AB injury and secondary dry eye. We demonstrated that AB injury induced activation of the TLR4-MyD88 pathway, leading to imbalanced NLRP3 and NLRP6 via the activation of caspase-8 signaling. DS worsened ocular surface disorders post-AB injury by magnifying this phenomenon. Caspase-8 signaling promoted NLRP3 upregulation via the nuclear factor (NF)-κB pathway, while NLRP6 suppressed NF-κB activation. Our findings also revealed that TLR4-MyD88 knockout can alleviate AB-induced or DS-worsened ocular surface disorders, shedding light on the potential therapeutic strategies in the future for AB injury. Taken together, our findings demonstrate that AB promotes the TLR4-MyD88-caspase-8 axis to cause imbalanced NLRP3/NLRP6, and DS exacerbates ocular surface damage via magnifying this imbalance. Highlights: Innate immunity participates in the pathogenesis of alkali burn injury. The activation of TLR4-MyD88 signaling promotes imbalanced activation of NLRP3/NLRP6 via caspase-8 activation. Caspase-8 activation drives NLRP3 upregulation via the NF-κB pathway, while NLRP6 negatively regulates NF-κB translocation. The elimination of TLR4/MyD88 could alleviate ocular surface disorders post alkali burn.